A case of acute posterior multifocal placoid pigment epitheliopathy: clinical analysis and differential diagnosis (Ukrainian Journal of Ophthalmology, 2025)
Background: Acute posterior multifocal placoid pigment epitheliopathy (APMPPE) is a rare inflammatory disease, and the differential diagnostic assessment is essential for its adequate treatment.Purpose: To perform clinical analysis and differential diagnosis for a case of APMPPE.Material and Methods: We present a case of a 26-year-old woman with APMPPE. The patient underwent an eye examination which included visual acuity assessment, refractometry, tonometry, perimetry, biomicroscopy, direct and indirect ophthalmoscopy, optical coherence tomography (OCT), fundus photography, and fluorescein angiography (FA). Endonasal electrophoresis was conducted in a routine manner using azithromycin, a macrolide antibiotic.Results: OCT found numerous flat yellowish-white and grey-pink lesions in the posterior pole of the fundus at the level of the retinal pigment epithelium and choriocapillary layers. FA showed irregularly shaped non-fluorescent lesions, which began to exhibit faint fluorescence a few minutes after the dye injection. The differential diagnosis should include serpiginous choroiditis, Vogt-Koyanagi-Harada syndrome, geographical choroiditis, acute retinal pigment epitheliitis (Krill disease), and choroidal neoplasm.Conclusion: Acute posterior multifocal placoid pigment epitheliopathy is an acute-onset disease. If the disease is suspected, a thorough history is essential, and the differential diagnosis should be performed for early treatment and referral to an appropriate specialist. Patients with this disease should be followed since recurrences can occur.
Keywords: acute posterior multifocal placoid pigment epitheliopathy; differential diagnosis; treatment